Intracellular signaling pathways triggered by the stimulation of the G-coupled Protein Receptor GPR75 by 20-hydroxyeicosatetraenoic acid (20-HETE) in androgen independent prostate cancer cells - Cardenas, Sofía (2019)
20-HETE, the product of 20-hydroxylation of arachidonic acid by cytochrome P450 isoforms (CYP4F2 and CYP4A11), has a role in the oncogenesis of several human tumors. Recently, the GPR75 receptor has been identified as the target for 20-HETE. We have shown that androgen independent prostate cancer cells (PC-3) express GPR75. The aim of this study was to identify intracellular signaling molecules activated upon GPR75 stimulation by 20-HETE in PC-3 cells.Cells were incubated with 20-HETE (0.1 nM) in the presence or absence of the antagonist of the 20-HETE receptor, AAA (5 or 10 uM). Protein expression of the inducible focal adhesion protein Hydrogen Peroxide Inducible Clone-5 (HIC-5), the phosphorylated and total form of NF-kB, AKT, p38 MAP-Kinase (p38) and EGFR were assessed by western blot. Intracellular localization of p-AKT, NF-kB and PKCa were determined by immunofluorescence and subcellular fractionation. Migration of PC-3 cells incubated with diferentes inhibitors were evaluated by scratch wound healing assay. Results were analyzed using one-way ANOVA followed by Dunnet?s.Incubation with 20-HETE (2 h) increased the phosphorylation of EGFR, NF-kB and AKT by 146, 172 and 219%, respectively (vs control, p<0.01 for NF-kB, and p<0.001 for EGFR and AKT, n=3), and this was inhibited by AAA (vs 20-HETE alone, p<0.05 for NF-kB, p<0.01 for AKT and p<0.001 for EGFR). AAA alone increased p-38 phosphorylation by 248% (p<0.001 vs control, n=3). 20-HETE (1 h) induced the translocation of p-AKT to the nuclei (p<0.001, n=3) and promoted the redistribution of PKCa out of the nuclei (p<0.05, n=3) to the plasma membrane (p<0.001). Both effects were inhibited by AAA (vs 20-HETE, p<0.01 for AKT and p<0.05 for PKCa). AAA alone reduced the nuclear signal of p-AKT and NF-kB usually activated in tumoral cells (p<0.001 for both, n=3). Additionally, 20-HETE (12 h) increased by 150% the protein expression of Hic-5 (p<0.0001, n=5) and this was abolished by AAA (p<0.001).Our results show that 20-HETE modulates signaling pathways known to be deregulated in malignant cells through the GPR75-axis.